Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

The Palaeontological Heritage of Boulemane Between Illegal Looting and Geoconservation: Issues, Challenges and Solutions - Kawtar Ech-charay; Khadija Boumir; Susannah C. R. Maidment; Ahmed Oussou; Richard J. Butler; Mustapha Ouaskou; Abdessalam El Khanchoufi; Driss Ouarhache (Geoheritage, 2026)

Tree shade protection factors by Jacaranda mimosifolia: a summertime comparison of UV dosimetry and whole sky image analysis for residential urban environments - Nathan J. Downs; Stijn Dekeyser; Adrian Dawes; Alfio V. Parisi; Harry J. Butler; Nawin Raj; Ravinesh C. Deo; Joanna Turner; Damien Igoe; Charlene Jackson; Catherine Chinnock; Melanie J. Beckman-Downs (Urban Forestry & Urban Greening, 2026)

A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

A pragmatic framework for local operationalisation of national-level biodiversity impact mitigation commitments - Thomas B. Atkins; Natalie E. Duffus; Amber J. Butler; Hannah C. Nicholas; Sophus O.S.E. zu Ermgassen; Prue Addison; E.J. Milner-Gulland (Environmental Science & Policy, 2025)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Freshwater fish condition responses to hydrological disturbance are species‐ and scale dependent - Maxwell C. Mallett; Jason D. Thiem; Gavin L. Butler; Luke Carpenter‐Bundhoo; Mark J. Kennard (Journal of Fish Biology, 2025)
Modification of river flows is a major cause of freshwater fish population declines in many parts of the world. Identifying the precise mechanisms of these declines represents a significant challenge, as a range of stressors can simultaneously impact various components of fish health, fitness and population dynamics. Here we investigate the role of river flows and other biophysical factors on spatio‐temporal variation in freshwater fish body condition in Australia's highly modified Murray‐Darling Basin using three widely distributed native (Murray cod Maccullochella peelii , golden perch Macquaria ambigua and bony herring Nematalosa erebi ) and one introduced (common carp Cyprinus carpio ) species. Our aim was to uncover drivers of spatio‐temporal variation in fish condition at two spatial extents: at the basin scale, utilising a flow regime disturbance index, and at the river‐valley scale, employing individual flow gauge data to assess responses in fish condition to multiple measures of antecedent (365 day) flow. Linear mixed effects modelling revealed that at the basin scale, M. peelii and M. ambigua were in better condition in rivers with lower flow regime disturbance, and temporal trends in the condition of N. erebi , C. carpio and M. peelii reflected boom and bust dynamics related to wet and dry climate periods. At the river‐valley scale, mean antecedent daily flow magnitude was significantly positively related to the condition of M. peelii , M. ambigua and C. carpio , whereas the number of high‐flow days was negatively related to condition of N. erebi . Our study demonstrates that a simple body condition index calculated from routinely collected length–weight data is sensitive to multiple measures of hydrological disturbance in river systems that experience substantial temporal and spatial variability. We emphasise that studies considering multiple spatial scales are important for understanding complex scale‐dependent mechanisms influencing fish condition.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Muhammed A. Oyinlola; Mostafa Khorsandi; Noa B. Mayer; Natalie Butler; Jacey C. Van Wert; Erika J. Eliason; Richard Arsenault; Colin J. Brauner; Scott G. Hinch; Andre St-Hilaire (Climatic Change, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Accumulation and transport of nutrient and pollutant elements in riparian soils, sediments, and river waters across the Thames River Watershed, Connecticut, USA - Mark J. Butler; Brian C. Yellen; Oluyinka Oyewumi; William Ouimet; Justin B. Richardson (Science of The Total Environment, 2023)

Impact of dairy farms on groundwater quality in a productive basin in the northeast of the Pampean Plain, Argentina - F. Cellone; L. Santucci; G. Borzi; C. Tanjal; C. Di Lello; L. Butler; J. Córdoba; L. Lamarche; J. Galliari; E. Melendi; M.I. Delgado; E. Carol (Groundwater for Sustainable Development, 2023)

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Nicola J. Sullivan; Vaughn A. Bell; Ruth C. Butler; Roger Wallis; Remya Ramesh; D. Srinivasa Reddy; Andrew M. Twidle; Barry Bunn; C. Rikard Unelius; Lee-Anne M. Manning; David M. Suckling (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 µg of the ( S )-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus . Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species’ pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus . Combining the two mealybug species’ pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

For the birds? Contrasting pollination and breeding systems of the paintbrush lilies Scadoxus puniceus and S. membranaceus (Amaryllidaceae) - Hannah C. Butler; Ruth J. Cozien; Steven D. Johnson (Plant Systematics and Evolution, 2022)

Characterizing observed surface wind speed in the Hudson Bay and Labrador regions of Canada from an aviation perspective - Andrew C. W. Leung; William A. Gough; Ken A. Butler; Tanzina Mohsin; Micah J. Hewer (International Journal of Biometeorology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Hares in the long grass: increased aircraft related mortality of the Irish hare (Lepus timidus hibernicus) over a 30-year period at Ireland’s largest civil airport - Samantha Ball; Fidelma Butler; Anthony Caravaggi; Neil E. Coughlan; Gerry Keogh; Michael J. A. O’Callaghan; Ricky Whelan; Thomas C. Kelly (European Journal of Wildlife Research, 2021)
Collisions between wildlife and aircraft are a serious and growing threat to aviation safety. Understanding the frequency of these collisions, the identity of species involved, and the potential damage that can be inflicted on to aircraft aid mitigation efforts by airfield managers. A record of all animal carcasses recovered from Dublin International Airport, Ireland’s largest civil aviation airport, has been maintained since 1990 where strikes with the endemic Irish hare ( Lepus timidus hibernicus ), a protected subspecies of mountain hare, are of particular concern despite substantial management efforts from the airfield authority. The first strike event with a hare was recorded in 1997, and strike events have substantially increased since then, with a sharp increase recorded in 2011. Over a 30-year period, a total of 320 strike events with the Irish hare have been recorded at the airfield. To date, no strike event with a hare has resulted in damage to an aircraft. However, carcasses can present as a major attraction to avian scavenger species in addition to posing as a risk of causing foreign object damage in the event of an undetected carcass. Hare strikes are discussed in the context of the rate of civil aircraft movements, possible direct and indirect damage to aircraft, and airfield wildlife hazard management. Here, we demonstrate that not only are strike events increasing by 14% on an annual basis, but that the kinetic energy of such an event has the potential to cause significant damage to an aircraft.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Trace metals and metalloids in peri-urban soil and foliage across geologic materials, ecosystems, and development intensities in Southern California - Trevor J. Mackowiak; Ivan C. Mischenko; Mark J. Butler; Justin B. Richardson (Journal of Soils and Sediments, 2021)

The Long-Term Effect of Bleeding for Limulus Amebocyte Lysate on Annual Survival and Recapture of Tagged Horseshoe Crabs - David R. Smith; Joshua J. Newhard; Conor P. McGowan; C. Alyssa Butler (Frontiers in Marine Science, 2020)
In the U.S., 525,000 horseshoe crabs ( Limulus polyphemus ) per year have been captured during 2013–2017, brought to biomedical facilities, and bled to produce Limulus amebocyte lysate (LAL), then mostly released to the area of capture. The Atlantic States Marine Fisheries Commission estimates short-term bleeding-induced mortality to be 15% (4% to 30%), resulting in mortality of approximately 78,750 horseshoe crabs annually in recent years comprising a minor portion (<13%) of the up to one million annual coastwide landings dominated by harvest for bait. However, the long-term effect of bleeding for LAL on annual survival and spawning behavior is unknown; thus, results from short-term studies alone might underestimate bleeding effects at the population level. To address this knowledge gap, we analyzed data from the U.S. Fish and Wildlife horseshoe crab tagging database to estimate the differences in survival and recapture rates of bled and not bled horseshoe crabs tagged in the same years and geographic area. Contrary to expectation, survival was not lower for bled crabs compared to unbled crabs. Differences varied, but survival estimates tended to be higher for bled crabs than for unbled crabs. However, biomedical culling and selection for younger or healthier animals could have resulted in biomedically tagged individuals representing a healthier subset of the overall population with subsequent higher survival. Furthermore, the tagging analysis revealed a post-bleeding reduction in capture probability, which could indicate decreased spawning activity, evident in males more than females. Continued tagging of bled and unbled crabs in the same geographic area while recording age class and sex will contribute to the further resolution of LAL production’s effect on horseshoe crab populations.

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

The multi-element stoichiometry of wet eucalypt forest is transformed by recent, frequent fire - Orpheus M. Butler; James J. Elser; Tom Lewis; Sarah C. Maunsell; Mehran Rezaei Rashti; Chengrong Chen (Plant and Soil, 2020)

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Evaluation of heat stress and cumulative incidence of acute kidney injury in sugarcane workers in Guatemala - Jaime Butler-Dawson; Lyndsay Krisher; Hillary Yoder; Miranda Dally; Cecilia Sorensen; Richard J. Johnson; Claudia Asensio; Alex Cruz; Evan C. Johnson; Elizabeth J. Carlton; Liliana Tenney; Edwin J. Asturias; et al. (International Archives of Occupational and Environmental Health, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Analytical performance of a platform for point-of-care CRP testing in adults consulting for lower respiratory tract infection in primary care - Veerle Matheeussen; Viviane Van Hoof; Katherine Loens; Christine Lammens; Anouk Vanderstraeten; Samuel Coenen; Chris C. Butler; Paul Little; Theo J. M. Verheij; Herman Goossens; Margareta Ieven (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Productivity dominated by picoplankton in a macro‐tidal tropical estuary, Darwin Harbour - D. Purcell‐Meyerink; J. Fortune; E. C. V. Butler (New Zealand Journal of Botany, 2017)
Productivity around the tropical coast of North Australia has been considered to be dominated by phytoplankton. The phytoplankton encompasses a large taxon which, dependent on the source definition, can vary significantly. Traditionally, they would only include pelagic photosynthetic organisms (autotrophic), yet more recently the definition is being revised to include heterotrophic organisms. Recent advancements in oceanography over the past three decades have found the prevalence in the global ocean of cyanobacteria of sizes ranging from 0.5–1.5 µm. Two cyanobacterial genera Synechoccocus and Prochlorococcus are now recognised to dominate phytoplankton cell counts and biomass specifically in the oligotrophic tropical and subtropical oceans. This study is the first to identify the importance of picoplankton as a foremost contributor to productivity in a macro‐tidal ecosystem in Northern Tropical Australia. Picoplankton was found to be the dominant group of primary producers (> 99% or 6 × 10 9 cells/L) within the phytoplankton in Darwin Harbour during the dry season of 2013. The larger phytoplankton > 2 µm contributed ( 2 cells/L) of the population. This study further defines the influences on this dynamic system that would allow the picoplankton community to thrive, highlighting the complexity of this nitrogen‐limited system, where nutrient cycling, including nitrogen fixation mediated possibly through the microbial community, plays a pertinent role. Other environmental influences include spring tides, spatial variation and increased turbidity which benefits heterotrophy over autotrophy in this ecosystem.

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Isolation and characterization of an interactive culture of two Paenibacillus species with moderately thermophilic desulfurization ability - Jia Wang; Batzaya Davaadelger; Joelle K. Salazar; Robert R. Butler; Jean-François Pombert; John J. Kilbane; Benjamin C. Stark (Biotechnology Letters, 2015)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Response of Female Frankliniella occidentalis (Pergande) to Visual Cues and Para-anisaldehyde in a Flight Chamber - Melanie M. Davidson; Ruth C. Butler; David A. J. Teulon (Journal of Insect Behavior, 2012)

Relative humidity at Armagh Observatory, 1838–2008 - C. J. Butler; A. M. García‐Suárez (International Journal of Climatology, 2012)
We present a calibrated atmospheric humidity series for Armagh Observatory, Northern Ireland. Beginning in 1838 and continuing to the present day, this series is believed to be the longest presented so far. Daily wet‐bulb and dry‐bulb temperature readings are corrected for the time of reading and for known instrumental errors to determine mean monthly, seasonal and annual relative humidity (RH) at 09:00 GMT from 1838 to 2008 and at 21:00 GMT from 1844 to 1964. The mean seasonal and annual time series of RH at this site show only marginal evidence for a trend in RH since the 1880s, however, there is significant decadal and multi‐decadal variability, some of which appears to be cyclic. Wavelet analysis indicates the presence of two quasi‐periodic components in RH, one ranging from 23.4 to 25.5 years and the other from 36 to 51 years. We discuss potential physical origins of these cycles such as changes in the atmospheric and thermohaline circulation and the solar magnetic cycle. There is a small but significant anti‐correlation between RH and northerly winds. Two conspicuous peaks in RH during the 19th century coincide with major infestations of potato blight in Ireland. Copyright © 2011 Royal Meteorological Society

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Auditory facilitation of visual-target detection persists regardless of retinal eccentricity and despite wide audiovisual misalignments - Ian C. Fiebelkorn; John J. Foxe; John S. Butler; Sophie Molholm (Experimental Brain Research, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Disease avoidance influences shelter use and predation in Caribbean spiny lobster - Donald C. Behringer; Mark J. Butler (Behavioral Ecology and Sociobiology, 2010)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Farmers’ objectives toward their woodlands in the upper Midwest of the United States: implications for woodland volumes and diversity - W. Keith Moser; Earl C. Leatherberry; Mark H. Hansen; Brett J. Butler (Agroforestry Systems, 2009)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Wild turkey (Meleagris gallopavo) detectability from helicopters and ramifications for estimating abundance - Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Stephen J. DeMaso (European Journal of Wildlife Research, 2008)

Analyses of a multi-parent population derived from two diverse alfalfa germplasms: testcross evaluations and phenotype–DNA associations - I. J. Maureira-Butler; J. A. Udall; T. C. Osborn (Theoretical and Applied Genetics, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Finite-Element Stress Analysis of a Multicomponent Model of Sheared and Focally-Adhered Endothelial Cells - Michael C. Ferko; Amit Bhatnagar; Mariana B. Garcia; Peter J. Butler (Annals of Biomedical Engineering, 2007)

Soil temperatures at Armagh Observatory, Northern Ireland, from 1904 to 2002 - A. M. García-Suárez; C. J. Butler (International Journal of Climatology, 2006)

Accounting for body condition improves allometric estimates of resting metabolic rates in fasting king penguins, Aptenodytes patagonicus - A. Fahlman; L. G. Halsey; P. J. Butler; D.R. Jones; A. Schmidt; S. Durand; G. Froget; C. -A. Bost; A. J. Woakes; C. Duchamp; Y. Handrich (Polar Biology, 2006)

Stable isotope analysis of production and trophic relationships in a tropical marine hard-bottom community - Donald C. Behringer; Mark J. Butler (Oecologia, 2006)

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Assessment of genetic diversity in isolates of Ciborinia camelliae Kohn from New Zealand and the United States of America - R. F. van Toor; H. J. Ridgway; R. C. Butler; M. V. Jaspers; A. Stewart (Australasian Plant Pathology, 2005)

America's Family Forest Owners - Brett J. Butler; Earl C. Leatherberry (Journal of Forestry, 2004)
The number of family forest owners in the conterminous United States increased from 9.3 million in 1993 to 10.3 million in 2003, and these owners now control 42% of the nation's forestland. The reasons why people own forestland are diverse. Some of the more common ones are aesthetic enjoyment, the tract is part of a farm or home site, and to pass the land on to heirs. Half of the family forest owners have harvested trees, but only 3% of them have a written forest-management plan. Trends in owners' ages and future land-use intentions suggest widescale transfers of family forestland in the near future.

Fitting fertilisation kinetics models for free-spawning marine invertebrates - C. A. Styan; A. J. Butler (Marine Biology, 2000)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Zotepine in the prevention of recurrence: a randomised, double-blind, placebo-controlled study for chronic schizophrenia - S.J. Cooper; A. Butler; J. Tweed; C. Welch; J. Raniwalla (Psychopharmacology, 2000)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)

Effect of contraction strength on responses in biceps brachii and adductor pollicis to transcranial magnetic stimulation - J. L. Taylor; Gabrielle M. Allen; Jane E. Butler; S. C. Gandevia (Experimental Brain Research, 1997)

Interstitial fluid flow in tendons or ligaments: A porous medium finite element simulation - S. L. Butler; S. S. Kohles; R. J. Thielke; C. Chen; R. Vanderby (Medical & Biological Engineering & Computing, 1997)

Quantified elemental changes inAspidisca cicada andVorticella convallaria after exposure to aluminium, copper, and zinc - J. V. Abraham; R. D. Butler; D. C. Sigee (Protoplasma, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Temporal patterns and transport processes in recruitment of spiny lobster ( Panulirus argus ) postlarvae to south Florida - C. A. Acosta; T. R. Matthews; M. J. Butler IV. (Marine Biology, 1997)

The effect of thyroid hormones on the aerobic development of locomotor and cardiac muscles in the barnacle goose - K. E. Deaton; C. M. Bishop; P. J. Butler (Journal of Comparative Physiology B, 1997)

Methyl parathion persistence in soil following simulated spillage - L. C. Butler; D. C. Staiff; J. E. Davis (Archives of Environmental Contamination and Toxicology, 1981)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)